A SEMANTIC ANALYSIS OF FIVE NEAR-SYNONYMOUS ARABIC VERBS: JA’A, ATA, AQBAL, HADARA AND QADIMA (The Journal of Interdisciplinary Human Studies, 2026)
The Arabic language is renowned for its lexical richness, particularly inthe domain of near-synonyms (اللغوية الفروق). This paper examines the semantic distinctionsamong five Arabic verbs that are commonly translated as «to come» in English: jaʼa (جاء),ata (أتى), aqbala (أقبل), ḥaḍara (حضر), and qadima (قدم). Drawing upon classical Arabiclexicography, Qurʼanic usage, and modern linguistic scholarship, the study employs acomparative analytical method to identify the distinctive semantic features, pragmaticcontexts, and stylistic nuances of each verb. The findings reveal that despite their apparentsynonymy, each verb carries unique connotations related to manner, purpose, distance,formality, and aspectual perspective. The study contributes to the field of Arabic lexicalsemantics and has implications for Qurʼanic exegesis, Arabic language pedagogy, andtranslation studies.
Keywords: Arabic near-synonyms; lexical semantics; verbs of motion; furuq lughawiyya; Qurʼanic vocabulary; Arabic linguistics